Securing IM and P2P applications for the enterprise - Piccard, Paul L.; Sachs, Marcus H. (Rockland, MA : Syngress Pub., 2006)
This book is for system administrators and security professionals who need to bring now ubiquitous IM and P2P applications under their control. Many businesses are now taking advantage of the speed and efficiency offered by both IM and P2P applications, yet are completely ill-equipped to deal with the management and security ramifications. These companies are now finding out the hard way that these applications which have infiltrated their networks are now the prime targets for malicious network traffic. This book will provide specific information for IT professionals to protect themselves from these vulnerabilities at both the network and application layers by identifying and blocking this malicious traffic. * A recent study by the Yankee group ranked "managing and securing IM and P2P applications" as the #3 priority for IT managers in 2004 * The recently updated SANS/FBI top 10 list of vulnerabilities for computers running Microsoft Windows contained both P2P and IM applications for the first time * The recently released Symantec Threat Assessment report for the first half of 2004 showed that 19 of the top 50 virus threats targeted IM or P2P applications. Despite the prevalence of IM and P2P applications on corporate networks and the risks they pose, there are no other books covering these topics.
Instant messaging Applications; Introduction; AOL Instant Messanger; Yahoo! messanger; MSN Messanger; ICQ; Trillian, Google Talk, and Web-based Clients; Skype; Part II: Peer to Peer Networks; Introduction; Gnutella Architecture; eDonkey and eMule; BitTorrent; FastTrack; part III: Internet Chat Relays; IRC Networks and Security; Global IRC Security; Common IRC Clients by OS; Index.
Includes index.
Keywords: Instant messaging -- Security measures; Electronic mail messages -- Security measures; Peer-to-peer architecture (Computer networks); Computer security; Electronic books